Factores relacionados al destete precoz en madres con niños menores de 6 meses de vida, que acuden al Centro de Salud N° 2 de la ciudad de Loja. - Pesántez Torres, Juan Diego (2017)
The World Health Organization (WHO) recommends exclusive breastfeeding during the first six months of life as it is the ideal way to provide young children with the nutrients they need for healthy growth and development, but according to The last national maternal and child survey in Ecuador, the average time of exclusive breastfeeding is 3 months, with a prevalence of 39.6%. The present investigation was carried out to mothers with children under six months attending medical care at Centro de Salud N ° 2 of the city of Loja "Hugo Guillermo Gonzales" had a transversal, prospective and descriptive approach, and it was decided to determine The factors related to early weaning in mothers with children under 6 months of age, 482 mothers participated in the study, the survey was applied as a technique and the instrument was the questionnaire, the analysis was performed based on the bibliographic review; The results show that; The age at which exclusive breastfeeding is most frequently interrupted is at the fifth month of life, which represents 10%, working mothers indicated that the socioeconomic factor that led to the interruption of exclusive breastfeeding was the Difficulty due to work, and study hours in the case of mothers who are studying and as the main biological factor insufficient milk production and alterations in the nipple mastitis. In addition to having an erroneous knowledge about exclusive breastfeeding. KEY WORDS: preterm weaning, exclusive breastfeeding, children under 6 months.